AB0129 Mechanisms of t cell recruitment in lupus nephritis. (23rd January 2014) - Klocke, J. R.; von Spee-Mayer, C.; Enghard, P.; Riemekasten, G.
Abstract : Background: Local T cell infiltration is considered to play an important role in the pathogenesis of lupus nephritis (LN), one of the major complications of Systemic Lupus Erythematosus (SLE). The renal inflitrating cells can also be found in high numbers in the urine of patients with active LN, however little is known about how these cells are recruited into the inflamed kidney. Objectives: Identifying how conventional CD4+ and CD8+ T cells and regulatory T cells (Treg) are recruited into the inflamed kidney in LN. Methods: Serum and urine samples of 98 SLE patients were analyzed for 17 chemokines using multiplex assays. Based on the assay's results a group of 8 corresponding chemokine receptors (CCR1 - 6, CXCR3 and CXCR6) was chosen, whose frequencies on urinary T cells were subsequently determined in 7 patients with acute LN by flowcytometry. Results: 10 chemokines* were significantly elevated in the urine of patients with active LN when compared to the control group. The other 7 chemokines° showed no significant differences between the groups. CCR5 and CXCR3 were the most prominent receptors on both urinary CD4+ and CD8+ T cells, although CD4+ T cells also expressed high amounts of CCR4 and CCR6. The chemokine receptor expression on CD4+FoxP3+CD127- Treg differed from conventional CD4+ T cells as well. Treg expressed significantly more CCR4 and significantly less CXCR6. *: CCL2, CCL3, CCL4, CCL5, CCL7, CCL8, CCL11, CXCL9, CXCL10 and CXCL16 °: CCL1, CCL17, CCL20, CCL22, CXCL1, CXCL5 and CXCL11 Conclusions: CCR5 and CXCR3 are the primary receptors in the mechanism of recruiting all T cells into the inflamed kidney. Key chemokines for T cell attraction are CCL4, CCL5 and CCL8 as well as CXCL9 and CXCL10. However, at least for CD4+ T cells, there are secondary pathways of recruitment involving CCR4 and CCR6. Also, Treg recruitment seems to rely more on CCR4 than that of conventional CD4+ T cells. Disclosure of Interest: None Declared